2014
DOI: 10.1001/jamapediatrics.2013.2752
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Human Papillomavirus Vaccination Among US Adolescents

Abstract: IMPORTANCE Since licensure of the human papillomavirus (HPV) vaccine in 2006, HPV vaccine coverage among US adolescents has increased but remains low compared with other recommended vaccines. OBJECTIVE To systematically review the literature on barriers to HPV vaccination among US adolescents to inform future efforts to increase HPV vaccine coverage. EVIDENCE REVIEW We searched PubMed and previous review articles to identify original research articles describing barriers to HPV vaccine initiation and compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

40
720
2
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 759 publications
(770 citation statements)
references
References 75 publications
(252 reference statements)
40
720
2
8
Order By: Relevance
“…These studies have found that public insurance status, Hispanic race, lower family income, having received flu vaccine, increased perceived vaccine effectiveness, peer acceptance and anticipated inaction regret, were associated with increased vaccine uptake or uptake intent in males (6)(7)(8)(9)(10).…”
Section: Most Published Research On Factors Associated With Hpv Vaccimentioning
confidence: 99%
“…These studies have found that public insurance status, Hispanic race, lower family income, having received flu vaccine, increased perceived vaccine effectiveness, peer acceptance and anticipated inaction regret, were associated with increased vaccine uptake or uptake intent in males (6)(7)(8)(9)(10).…”
Section: Most Published Research On Factors Associated With Hpv Vaccimentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] Although vaccination intent was increased, it was neither sustained nor translated into vaccination behavior. Furthermore, there has been speculation that parents from different ethnic and socioeconomic groups may face different barriers to vaccination and thus require different intervention strategies, 17,19 a critical point in the context of disparate HPV disease outcomes.…”
mentioning
confidence: 99%
“…2 These studies, including our own, have typically examined the relationship between parents' vaccination beliefs, their intention to vaccinate their adolescents, and adolescents' ultimate vaccination status. [3][4][5][6] This research has been important for identifying potentially modifiable barriers to HPV vaccination, such as parents' need for more information and their perception that their children's risk of HPV infection is low. [3][4][5][6] However, despite the large volume of existing literature, basic gaps in our understanding of parents' decision making processes remain.…”
mentioning
confidence: 99%